2019
DOI: 10.1088/2053-1591/ab143b
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of In2S3 thin films measured using surface photovoltage spectroscopy

Abstract: In recent years, In 2 S 3 thin films were widely used as buffer/window layer in thin film solar cells as an alternative to toxic CdS. In the present work, we demonstrate the potential of surface photovoltage spectroscopy for estimation of minority carrier diffusion length, band gap energy and refractive index of thermally evaporated In 2 S 3 thin films. The estimated minority carrier diffusion length of In 2 S 3 thin films from SPV measurements were 0.112 μm and 0.052 μm for films annealed at 250 and 300 °C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…where, S 0 we fitted as 0.8 cm/s and 2.5 cm/s; n 0 is the equilibrium doping density, 3.6 × 10 11 cm −3 and 17.5 × 10 11 cm −3 in In 2 S 3 films annealed at 250 °C and 300 °C respectively. The equilibrium doping density of the films was estimated from the carrier mobility, 16 cm 2 /Vs and 4 cm 2 /Vs for films annealed at 250 °C and 300 °C [30] and respective resistivity of these samples are 1.06 × 10 6 Ω•cm and 0.89 × 10 6 Ω•cm, determined using Ohmic contacts. The fitted S int values (relation 5) in the LITG experiment increased from 3.1 × 10 5 to 16.3 × 10 5 cm/s and 1.2 × 10 5 to 6.7 × 10 5 cm/s with increase of ∆N in the layers.…”
Section: Resultsmentioning
confidence: 99%
“…where, S 0 we fitted as 0.8 cm/s and 2.5 cm/s; n 0 is the equilibrium doping density, 3.6 × 10 11 cm −3 and 17.5 × 10 11 cm −3 in In 2 S 3 films annealed at 250 °C and 300 °C respectively. The equilibrium doping density of the films was estimated from the carrier mobility, 16 cm 2 /Vs and 4 cm 2 /Vs for films annealed at 250 °C and 300 °C [30] and respective resistivity of these samples are 1.06 × 10 6 Ω•cm and 0.89 × 10 6 Ω•cm, determined using Ohmic contacts. The fitted S int values (relation 5) in the LITG experiment increased from 3.1 × 10 5 to 16.3 × 10 5 cm/s and 1.2 × 10 5 to 6.7 × 10 5 cm/s with increase of ∆N in the layers.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the In2S3 films were deposited at a temperature of 150 °C by applying a 20 W RF power, and subsequently, a post thermal annealing process was applied to as-deposited films at the temperatures of 350 °C and 450 °C under argon (Ar) atmosphere in a tube furnace, outside the deposition chamber unlike the existing studies in the literature. As a result of our literature review, we concluded that a lot of work has been done on thermal annealing of In2S3 films in the literature [19,[35][36][37][38][39]. However, as we mentioned above, in all these studies, the films were deposited by mostly thermal evaporation and CBD methods.…”
Section: Introductionmentioning
confidence: 85%
“…The schematic diagram of the SPV measurement configuration was similar to what was previously described in the paper [21].…”
Section: Methodsmentioning
confidence: 99%